Halloysite- and Montmorillonite-Loaded Scaffolds as Enhancers of Chronic Wound Healing - Giuseppina Sandri; Angela Faccendini; Marysol Longo; Marco Ruggeri; Silvia Rossi; Maria Cristina Bonferoni; Dalila Miele; Adriele Prina-Mello; Carola Aguzzi; Cesar Viseras; Franca Ferrari (MDPI AG, 2020)
The increase in life expectancy and the increasing prevalence of diabetic disease and venous insufficiency lead to the increase of chronic wounds. The prevalence of ulcers ranges from 1% in the adult population to 3−5% in the over 65 years population, with 3−5.5% of the total healthcare expenditure, as recently estimated. The aim of this work was the design and the development of electrospun scaffolds, entirely based on biopolymers, loaded with montmorillonite (MMT) or halloysite (HNT) and intended for skin reparation and regeneration, as a 3D substrate mimicking the dermal ECM. The scaffolds were manufactured by means of electrospinning and were characterized for their chemico-physical and preclinical properties. The scaffolds proved to possess the capability to enhance fibroblast cells attachment and proliferation with negligible proinflammatory activity. The capability to facilitate the cell adhesion is probably due to their unique 3D structure which are assisting cell homing and would facilitate wound healing in vivo.